The effectiveness of a training program to develop the functional competence of a sample of workers in the field of student counseling in Hail (Journal of the College of Basic Education, 2022)
Objective: The current research aims to develop the functional competence of a sample of student counselors, and the importance of the research comes from the importance that the field of student counseling represents in the education system in the Kingdom. It enables them to develop their skills and overcome their functional weaknesses.